Will epigenetics be a key player in crop breeding? - Tonosaki, Kaoru; Fujimoto, Ryo; Dennis, Elizabeth S.; Raboy, Victor; Osabe, Kenji (Frontiers in Plant Science, 2022)
If food and feed production are to keep up with world demand in the face of climate change, continued progress in understanding and utilizing both genetic and epigenetic sources of crop variation is necessary. Progress in plant breeding has traditionally been thought to be due to selection for spontaneous DNA sequence mutations that impart desirable phenotypes. These spontaneous mutations can expand phenotypic diversity, from which breeders can select agronomically useful traits. However, it has become clear that phenotypic diversity can be generated even when the genome sequence is unaltered. Epigenetic gene regulation is a mechanism by which genome expression is regulated without altering the DNA sequence. With the development of high throughput DNA sequencers, it has become possible to analyze the epigenetic state of the whole genome, which is termed the epigenome. These techniques enable us to identify spontaneous epigenetic mutations (epimutations) with high throughput and identify the epimutations that lead to increased phenotypic diversity. These epimutations can create new phenotypes and the causative epimutations can be inherited over generations. There is evidence of selected agronomic traits being conditioned by heritable epimutations, and breeders may have historically selected for epiallele-conditioned agronomic traits. These results imply that not only DNA sequence diversity, but the diversity of epigenetic states can contribute to increased phenotypic diversity. However, since the modes of induction and transmission of epialleles and their stability differ from that of genetic alleles, the importance of inheritance as classically defined also differs. For example, there may be a difference between the types of epigenetic inheritance important to crop breeding and crop production. The former may depend more on longer-term inheritance whereas the latter may simply take advantage of shorter-term phenomena. With the advances in our understanding of epigenetics, epigenetics may bring new perspectives for crop improvement, such as the use of epigenetic variation or epigenome editing in breeding. In this review, we will introduce the role of epigenetic variation in plant breeding, largely focusing on DNA methylation, and conclude by asking to what extent new knowledge of epigenetics in crop breeding has led to documented cases of its successful use.